Analysis of Teacher Time Management and Its Impact on Learning Effectiveness at SDIT Al Irsyad Al Islamiyyah Lemahabang - Suhandinda, Suhandinda; Nurkholis, Nurkholis; Putra, Nugraha Permana (Jurnal Ragam Pengabdian, 2026)
This study aims to describe teachers' time management in the learning process, examine its implications for student engagement, and identify factors influencing teachers' ability to manage instructional time. This study employed a qualitative descriptive approach. Data were collected through classroom observations, semi-structured interviews, and documentation involving teachers, the principal, and students. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that teachers' time management is implemented through instructional time planning, allocation of time for each learning stage, classroom time control, prioritization of activities, and adjustment of learning activities when unexpected conditions occur. Effective time management contributes to a more orderly and well-directed learning process, appropriate transitions between activities, and reduced instructional time loss. Furthermore, teachers' time management has implications for student engagement by providing opportunities for students to ask questions, respond to teachers, participate in discussions, complete learning tasks, and maintain concentration during learning activities. The study also identifies classroom conditions, student disruptions, the school environment, and school activities as factors that may affect the use of instructional time. Teachers respond to these factors through flexible and situational time-management strategies. The study concludes that teachers' time management is an important pedagogical competence that connects instructional planning, classroom management, student engagement, and the achievement of learning objectives.